Australian general practice registrars’ experiences of training, well-being and support during the COVID-19 pandemic: a qualitative study - Lucie Walters; Jill Benson; Isabella White; Taryn Elliott (BMJ Open)
Objectives Providing well-supported general practice (GP) training is fundamental to strengthen the primary health workforce. Research into the unique needs of GP registrars during disasters is limited. Registrar burnout and insufficient support have been associated with personal and professional detrimental effects. This study aims to explore the experiences of Australian GP registrars with learning, well-being and support from their training organisation during the COVID-19 pandemic, and to guide training organisation efforts to support registrars through future disasters.Setting Interviews were conducted via Zoom.Participants Fifteen GP registrars from South Australia, Victoria and New South Wales who had experienced community-based GP training in both 2019 (prepandemic) and 2020 (early pandemic).Outcome measures Training, well-being and support experiences were explored. Interviews were recorded and transcribed and themes analysed.Results Diverse experiences were reported: changes included telehealth, online tutorials, delayed examinations and social restrictions. Social and professional connections strongly influenced experiences. Personal and training factors were also important. Additional GP training organisation support was minimally needed when strong connections were in place.Conclusions This study identifies aspects of support which shaped registrars’ diverse experiences of COVID-19, particularly regarding professional and social connections. Findings illustrate the importance of broad principles around supporting registrar well-being. Particularly significant aspects of support include connection to educational mentors such as supervisors and medical educators; connection and culture within practices; opportunities to share clinical experiences; and connection to personal social supports. Participation in this global disaster contributed to registrars’ developing professionalism. GP training organisations are positioned to implement monitoring and supports for registrars through disasters. Although registrars may not require significant GP training organisation intervention where powerful professional and personal connections exist, strong foundational GP training organisation supports can be established and augmented to support registrars in need before and during future disasters. These findings contribute to the global developing field of knowledge of registrar training and well-being needs during crises.